Buckling design of axially compressed steel silos on discrete supports: Comparison between FE‐calculated buckling strengths and Eurocode interaction curves. Issue 1 (8th February 2018) - Jansseune, Arne; Belis, Jan; De Corte, Wouter
Abstract: This paper compares the buckling strengths derived from a validated shell‐based FEM model of discretely supported axially compressed silos with the interaction curves given in EN 1993‐1‐6 for axial compression. The buckling strengths were numerically determined for a wide range of geometries and yield strengths, considering two configuration types of discretely supported steel silos: with engaged columns and partial‐height U‐shaped longitudinal stiffeners. For these types, remarkably good correspondence was found between the numerical results of discretely supported steel silos and the interaction curves for uniformly compressed cylindrical steel silos, although unconservative in many cases.